Qualitative floristic survey in a riparian semideciduous seasonal forest fragment in Pouso Alegre - MG (Research, Society and Development, 2022)
Human actions have intensified the conversion of natural environments into modified areas, causing habitat fragmentation and changing environmental quality. The presence of riparian forests in hydrographic basins is essential for the maintenance of hydrological and ecological processes. Because they are vegetation located in areas that are essential for preservation against soil erosion, silting, protection of the course of rivers and springs, riparian forests are Permanent Preservation Areas, and must be protected and restored in case of degradation. Thus, the floristic survey is an important tool for watershed management, supporting ecological restoration projects. Therefore, the objective was to carry out a qualitative floristic survey in a riparian Semideciduous Seasonal Forest fragment, located in the municipality of Pouso Alegre, south of Minas Gerais. Vegetation was evaluated using the walking method. All arboreal individuals that presented visible reproductive structures and diameter at breast height equal to or greater than 5 cm were sampled. The botanical material was herborized and deposited in the UNIVÁS herbarium. The species were identified with the help of taxonomic keys and specialized bibliographies. Twenty-three species from 15 different families were identified. It is observed the predominance of pioneer species, being, therefore, an environment that suffered recent disturbances. Most species show zoochoric dispersion, which is important for ecological corridors. The list of species generated may, in the future, be added to projects aimed at forest restoration in the municipality of Pouso Alegre and in the southern region of Minas Gerais.